Front Cover: Synthesis of Unsymmetrical Squaramides as Allosteric GSK‐3β Inhibitors Promoting β‐Catenin‐Mediated Transcription of TCF/LEF in Retinal Pigment Epithelial Cells (ChemMedChem 24/2022). (16th December 2022) - Carullo, Gabriele; Bottoni, Laura; Pasquini, Silvia; Papa, Alessandro; Contri, Chiara; Brogi, Simone; Calderone, Vincenzo; Orlandini, Maurizio; Gemma, Sandra; Varani, Katia; Butini, Stefania; Galvagni, Federico; et al.
Abstract : The Front Cover shows the sustainable approach used to develop new unsymmetrical squaramides acting as allosteric GSK3β inhibitors, promoting TCF‐LEF transcription in retinal pigment epithelial ARPE‐19 cells. This work highlights how green chemistry coupled with computational and biological studies could be a valuable strategy for developing interesting pharmacological tools, activating neuroprotective pathways, and useful in retinal diseases associated with inflammatory/oxidative damage. More information can be found in the Research Article by Gabriele Carullo, Stefania Butini et al.